PENGARUH STATUS SOSIAL EKONOMI ORANG TUA DAN MOTIVASI ORANG TUA TERHADAP TINGKAT PENDIDIKAN ANAK PEDAGANG TOKO/KIOS DI PASAR RAYA KOTA PADANG (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2015)
The preliminary study toward the Merchants at Pasar Raya Padang, showed that the level of education of their children was still low. It was indicated by limited number of children who graduated from Senior High School and a few of them graduated from University. This condition was influenced by parents’ education, income, and motivation. This research was aimed to discovered: 1) the influence of parents’ level of education toward their income in Pasar Raya Padang, 2) the influence of parents’ level of education and income toward their motivation in Pasar Raya Padang, 3) the influence of parents’ level of education, income, and motivation toward their children level of education in Pasar Raya of Padang. The research was conducted under ex-post-facto design. The population was merchants stores with total number 2.337 and the sample was 343 which was taken by using purposive sampling. The data was collected through the questioner given to the sample which then analyzed statistically using path analysis. The data analysis showed that 1) parents’ level of education significantly influenced their income. It showed that the parents’ level of income was influenced by the level of education. 2) Parents’ level of education significantly influenced their motivation. It showed that parents’ motivation was influenced by their level of income as well as their level of education. 3) Parents’ level of education, income and motivation significantly influenced their children level of education in Pasar Raya Padang.